pCO2 and pH regulation of cerebral blood flow - Yoon, SeongHun; Zuccarello, Mario; Rapoport, Robert M. (Frontiers in Physiology, 2012)
CO2 Serves as one of the fundamental regulators of cerebral blood flow. It is widely considered that this regulation occurs through pCO2-driven changes in pH of the cerebral spinal fluid, with elevated and lowered pH causing direct relaxation and contraction of the smooth muscle, respectively. However, some findings also suggest that pCO2 acts independently of and/or in conjunction with altered pH. This action may be due to a direct effect of cerebral spinal fluid pCO2 on the smooth muscle as well as on the endothelium, nerves, and astrocytes. Findings may also point to an action of arterial pCO2 on the endothelium to regulate smooth muscle contractility. Thus, the effects of pH and pCO2 may be influenced by the absence/presence of different cell types in the various experimental preparations. Results may also be influenced by experimental parameters including myogenic tone as well as solutions containing significantly altered HCO3- concentrations, i.e., solutions routinely employed to differentiate the effects of pH from pCO2. In sum, it appears that pCO2, independently and in conjunction with pH, may regulate cerebral blood flow.